Metal-solid oxide composite, method for preparing the same, and solid oxide battery including the same

By using a metal-solid oxide composite with a multi-nanowire structure as a fuel electrode material in a solid oxide battery, the problem of coarsening of metal particles at high temperatures is solved, and the performance and long-term reliability of the battery are improved.

CN119768941APending Publication Date: 2025-04-04SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380061075.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-17
Filing Date
2023-07-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When solid oxide batteries work for a long time at high temperatures, the metal in the fuel electrodes migrate along the ceramic surface, causing metal particles to coarse, reduce specific surface area and conductivity, and affect the performance and long-term reliability of the battery.

Method used

A metal-solid oxide composite composed of multiple nanowire parts, metal parts and central parts is used as fuel electrode materials, and is prepared by gas-liquid solid growth method to ensure that metal particles are prevented from coarsing at high temperatures and increase specific surface area.

Benefits of technology

Effectively prevent metal particles from coarsing at high temperatures, increase the specific surface area of ​​the fuel electrode, thereby improving the performance and efficiency of solid oxide batteries and improving the long-term reliability of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768941A_ABST
    Figure CN119768941A_ABST
Patent Text Reader

Abstract

The metal-solid oxide composite includes: a plurality of nanowire portions including a solid oxide electrolyte material; a metal portion at one end of each of the plurality of nanowire portions and including a metal; and a central portion connected to the other end of the nanowire portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2022-0169583 filed on December 7, 2022, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0021185 filed on February 17, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0002] The present disclosure relates to a metal-solid oxide composite, a method for preparing the same, and a solid oxide cell including the metal-solid oxide composite, wherein the solid oxide cell improves cell performance and efficiency by using a fuel electrode material having a structure in which coarsening is prevented during high temperature operation and specific surface area is increased without interfering with gas flow. Background Art

[0003] A solid oxide cell (SOC) is, for example, a solid oxide fuel cell (SOFC) or a solid oxide electrolyte cell (SOEC), and generates electrical energy through an electrochemical reaction of a cell (the cell is composed of an air electrode, a fuel electrode, and a solid oxide electrolyte having oxygen ion conductivity), or electrolyzes water and generates hydrogen through the reverse reaction of a solid oxide fuel cell.

[0004] The solid oxide cell has a configuration in which an air electrode and a fuel electrode are disposed on both sides of a solid oxide electrolyte having oxygen ion conductivity to supply air and fuel to the air electrode and the fuel electrode, respectively, through flow paths formed in a separator, thereby generating electricity or performing electrolysis by an electrochemical reaction.

[0005] Solid oxide cells generally use metal-ceramic based materials as fuel electrodes, which are mixtures of metal and ceramic (electrolyte material) with low resistance and economy. Fuel electrodes in which the two materials are mixed can provide high electronic conductivity and high ion conductivity as well as a wide interface.

[0006] However, due to the characteristics of solid oxide cells operating at high temperatures for long periods of time and the low affinity between the two materials, the metal in the fuel electrode migrates along the ceramic surface, causing metal particle coarsening through Ostwald ripening. The coarsening of metal particles can reduce the specific surface area, thereby reducing the three-phase interface, resulting in deterioration of conductivity. Therefore, the coarsening of metal particles is one of the main reasons for the deterioration of the characteristics and long-term reliability of solid oxide cells. Summary of the invention

[0007] Technical issues

[0008] One aspect of the present disclosure provides a solid oxide cell that improves cell performance and efficiency by using a fuel electrode material having a structure in which coarsening is prevented during high-temperature operation and a specific surface area is increased without disturbing gas flow.

[0009] Solutions to the problem

[0010] A metal-solid oxide composite according to one aspect includes: a plurality of nanowire portions including a solid oxide electrolyte material; a metal portion disposed on one end of each of the plurality of nanowire portions and including a metal; and a central portion connected to opposite ends of the nanowire portions.

[0011] The metal-solid oxide composite may have a shape in which each of the nanowire portions radially extends from the central portion, and a metal portion is disposed on a top of each of the nanowire portions.

[0012] The metal-solid oxide composite may have an average size of 0.5 μm to 10 μm.

[0013] The nanowire portion may have an average length of 0.2 μm to 3 μm and an average diameter of 10 nm to 500 nm.

[0014] The metal portion may substantially have a hemispherical shape and have an average size of 10 nm to 500 nm.

[0015] The solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0016] The metal part may include nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), gold (Au), copper (Cu), oxides thereof, or combinations thereof.

[0017] The metal-solid oxide composite may include 20 to 80 parts by weight of the metal based on 100 parts by weight of the solid oxide electrolyte material.

[0018] The metal-solid oxide composite may further include an interface portion disposed between the nanowire portion and the metal portion and including a mixture of the solid oxide electrolyte material and the metal of the metal portion.

[0019] A method for preparing a metal-solid oxide composite according to some embodiments of the present disclosure includes preparing the metal-solid oxide composite using a vapor-liquid-solid (VLS) growth method in which a metal is a catalyst and a vapor-phase precursor of a solid oxide electrolyte material is supplied to grow nanowires.

[0020] The gas-liquid-solid growth method may include: supplying a precursor of a solid oxide electrolyte material in a gas phase to a space under high temperature and low pressure; dissolving the precursor of the solid oxide electrolyte material in a metal in a liquid phase; continuously supplying the precursor of the solid oxide electrolyte material to reach a supersaturated state; and precipitating the supersaturated solid oxide electrolyte material as a solid phase to grow nanowires.

[0021] The high temperature and low pressure state may be a temperature of 500° C. to 1200° C. and a pressure of 0.03 atm to 1 atm.

[0022] The precursor of the solid oxide electrolyte material may include cerium chloride, cerium carbonate, cerium oxide, cerium nitride, gadolinium nitride, gadolinium chloride, gadolinium carbonate, gadolinium oxide, zirconium chloride, zirconium nitride, zirconium oxide, zirconium carbonate, yttrium chloride, yttrium nitride, yttrium oxide, yttrium carbonate, or a combination thereof.

[0023] The metal included in the metal part may include nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), gold (Au), copper (Cu), or a combination thereof.

[0024] A solid oxide cell according to another aspect includes: a solid oxide electrolyte; and a fuel electrode and an air electrode, the fuel electrode being located on one side of the solid oxide electrolyte and the air electrode being located on an opposite side of the solid oxide electrolyte.

[0025] The fuel electrode may include a metal-solid oxide composite, which includes: a plurality of nanowire portions including a solid oxide electrolyte material; a metal portion located at one end of each of the plurality of nanowire portions and including a metal; and a central portion connected to opposite ends of the nanowire portions.

[0026] The fuel electrode may further include fuel electrode material particles including nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), oxides thereof, or combinations thereof.

[0027] The fuel electrode may include solid oxide electrolyte particles, which include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0028] The air electrode may include an air electrode material including lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or a combination thereof.

[0029] The solid oxide electrolyte may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0030] The solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyte cell (SOEC), or both.

[0031] Advantageous Effects of the Invention

[0032] In solid oxide cells according to some embodiments of the present disclosure, by using a fuel electrode comprising a metal-solid oxide composite, the performance and efficiency of the solid oxide cell can be improved at least because coarsening is prevented during high temperature operation and the specific surface area is increased without disturbing gas flow. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and other aspects, features and other advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings.

[0034] Figure 1 is a perspective view showing a metal-solid oxide composite according to one aspect.

[0035] Figure 2 yes Figure 1 Magnified side view of region II.

[0036] Figure 3is a schematic diagram showing a modified embodiment of a solid oxide cell according to another aspect.

[0037] Figure 4 is a schematic diagram showing another modified embodiment of a solid oxide cell according to another aspect. DETAILED DESCRIPTION

[0038] Hereinafter, the present disclosure will be described in detail with reference to the accompanying drawings so that a person of ordinary skill in the art can practice. The drawings and descriptions are considered to be illustrative rather than restrictive in nature. Throughout the specification, the same reference numerals represent the same elements. In addition, the drawings are provided only to make the disclosed embodiments in this specification easy to understand, and are not to be construed as limiting the spirit disclosed in this specification, and it should be understood that the present embodiment includes all variations, equivalents and alternatives without departing from the scope and spirit of the present disclosure. In addition, some components are exaggerated, omitted or schematically depicted in the drawings, and the size of each component does not necessarily represent the actual size.

[0039] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “including” or “having”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.

[0040] Figure 1 is a perspective view showing a metal-solid oxide composite 10 according to one aspect, and Figure 2 yes Figure 1 Magnified side view of region II.

[0041] Reference Figure 1 and Figure 2 According to some embodiments of the present disclosure, the metal-solid oxide composite 10 includes: a plurality of nanowire portions 11 having a nanowire shape; a metal portion 12 disposed on one end of each of the plurality of nanowire portions 11; and a central portion 13 connected to the opposite end of each of the nanowire portions 11.

[0042] For example, the central portion 13 may have a substantially spherical shape.For example, the central portion 13 may be connected to at least two, at least three, at least four, at least five, at least ten, at least twenty, or at least fifty or more of the nanowire portions 11.

[0043] In addition, the nanowire portion 11 may have a shape extending radially from the central portion 13. Thus, for example, the metal-solid oxide composite 10 may have a shape of a chestnut cluster or a sea urchin in which thorns extend in various directions from the central portion 13 (the central portion 13 is a spherical structure). The nanowire portion may have a nanowire shape in which each of the cylindrical nanowire portions 13 may have a different length and a different diameter from each other, or all of the nanowire portions 13 may be substantially the same shape and substantially the same size.

[0044] It may be difficult to distinguish the boundary between the central portion 13 and the nanowire portion 11. However, the boundary between the central portion 13 and the nanowire portion 11 may be defined as a position where the diameter of the opposite end of the nanowire portion 11 away from the central portion is at least one time (e.g., at least two times, at least three times, at least four times, or at least five times) the maximum diameter of the metal portion 12 where the metal portion is attached to the nanowire portion 11.

[0045] Since the metal-solid oxide composite 10 has such a shape, when driven at high temperature, not only coarsening can be prevented but also the specific surface area of ​​the metal-solid oxide composite can be increased without disturbing gas flow, thereby improving the performance and efficiency of the solid oxide battery.

[0046] Hereinafter, the average size of the metal-solid oxide composite 10, the average size and composition of each constituent part of the metal-solid oxide composite 10, and the like are analyzed by taking a reflected electron image of the metal-solid oxide composite 10 with a scanning transmission electron microscope (STEM) or taking a HAADF image thereof with a scanning electron microscope (SEM) for analysis.

[0047] The average size of the metal-solid oxide composite 10, the average size and composition of each constituent part of the metal-solid oxide composite 10, etc. are measured by measuring at least 3, at least 5, or at least 10 metal-solid oxide composites 10 and calculating the average of the measured results.

[0048] In addition, the composition of each constituent part of the metal-solid oxide composite 10 can be measured by performing composition analysis on a reflection electron image using SEM or a HAADF image using STEM using an electron beam microanalyzer (EPMA). The composition analysis is performed by measuring at least 3, at least 5, or at least 10 points and calculating the average value of the measurement results. When the electron beam microanalyzer (EPMA) is used to perform composition analysis, etc., EDS (energy dispersive spectrometer), WDS (wavelength dispersive spectrometer), etc. can be used as an X-ray spectrometer.

[0049] The metal-solid oxide composite 10 may have an average size of 0.5 μm to 10 μm. Herein, the size of the metal-solid oxide composite 10 may be the longest distance among straight lines connecting one metal portion 12 and another metal portion 12 in a SEM image or a STEM image.

[0050] The nanowire portion 11 may have a nanowire shape and have an average length of 0.2 μm to 3 μm and an average diameter of 10 nm to 500 nm. Herein, the length of the nanowire portion 11 may be a distance from one end connected to the central portion 13 to the opposite end connected to the metal portion 12 on a SEM image or a STEM image, and the diameter of the nanowire portion 11 may be a length in a direction perpendicular to the length direction of the nanowire portion 11 measured at a middle (1 / 2) point between one end connected to the central portion 13 and the other end connected to the metal portion 12 on a SEM image or a STEM image.

[0051] The metal portion 12 may have a substantially spherical shape and have an average size or average diameter of 10 nm to 500 nm. The size or diameter of the metal portion 12 may be the maximum diameter among the diameters of the metal portion 12 in a direction perpendicular to the length direction of the nanowire portion 11 measured on a SEM image or a STEM image.

[0052] The nanowire portion 11 and the central portion 13 may include a solid oxide electrolyte material, and may include, for example, a single solid oxide electrolyte material.

[0053] Solid oxide electrolyte materials should have high oxygen ion conductivity and low electronic conductivity.

[0054] For example, the solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0055] The metal portion 12 may include a fuel electrode material.

[0056] The fuel electrode material can electrochemically oxidize the fuel and transfer the charge.

[0057] The fuel electrode material may include nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), oxides thereof, or combinations thereof.

[0058] In this case, the metal-solid oxide composite 10 may include a cermet in which a fuel electrode material and a solid oxide electrolyte material are combined. For example, when the solid oxide electrolyte material is yttria-stabilized zirconia (YSZ) and the fuel electrode material is nickel (Ni), the metal-solid oxide composite 10 may be a Ni / YSZ cermet, and when the fuel electrode material is ruthenium (Ru), the metal-solid oxide composite 10 may be a Ru / YSZ cermet.

[0059] The metal-solid oxide composite 10 may include 20 to 80 parts by weight of a metal as a fuel electrode material based on 100 parts by weight of a solid oxide electrolyte material. When the amount of the metal included is less than 20 parts by weight, an electrical conduction path may not be generated.

[0060] The metal-solid oxide composite 10 may further include an interface portion 14 between the nanowire portion 11 and the metal portion 12. The interface portion 14 includes a mixture of a solid oxide electrolyte material and a metal of a fuel electrode material.

[0061] As will be described later, when the metal-solid oxide composite 10 is formed by using a vapor-liquid-solid (VLS) growth method, an interface portion 14 in an intermediate form may be provided between the metal portion 12 including a metal and the nanowire portion 11 including a solid oxide electrolyte material.

[0062] The interface portion 14 has interface affinity with both the metal of the fuel electrode material and the solid oxide electrolyte material, and can improve the bonding strength between the metal portion 12 and the nanowire portion 11 even at high temperatures.

[0063] A method for preparing a metal-solid oxide composite according to some embodiments of the present disclosure includes preparing the metal-solid oxide composite using a vapor-liquid-solid (VLS) growth method.

[0064] The method for preparing a metal-solid oxide composite using a vapor-liquid-solid growth method includes supplying a vapor-phase precursor of a solid oxide electrolyte material using a liquid-phase metal as a catalyst to grow solid-phase nanowires.

[0065] For example, when a gas-liquid-solid growth method is used and a gas-phase precursor of a solid oxide electrolyte material is supplied into a space under a high temperature and low pressure state, the precursor of the solid oxide electrolyte material is dissolved in the liquid metal, and when the precursor of the solid oxide electrolyte material is continuously supplied to reach a supersaturated state, the supersaturated solid oxide electrolyte material is precipitated as a solid phase to grow nanowires.

[0066] Herein, since the nanowires grow at all interfaces where the metal exists, the metal-solid oxide composite finally prepared may have a shape such as a chestnut cluster or a sea urchin in which thorns extend in all directions from the center (the center is a spherical structure). Since the specific surface area is increased without hindering the air flow, the metal-solid oxide composite having such a structure can improve the performance and efficiency of the solid oxide battery.

[0067] In addition, since the gas-liquid-solid growth method is a process of precipitating a supersaturated solid oxide electrolyte material, when the process is stopped, an interface portion in the form of an intermediate can be formed between the metal and the synthesized nanowire structure. The interface portion has an interface affinity for both the metal and the solid oxide electrolyte material, and thus the bonding strength between the metal portion and the nanowire portion can be improved even at high temperatures.

[0068] In the gas-liquid-solid growth method, the high temperature and low pressure state may be a temperature of 500 to 1200° C. and a pressure of 0.03 to 1 atm. In the gas-liquid-solid growth method, when the temperature is less than 500° C., the metal catalyst may not be liquefied and the nanowire portion may not be synthesized.

[0069] Precursors of the solid oxide electrolyte material that can be used in the vapor-liquid-solid growth method may include cerium chloride, cerium nitride, cerium carbonate, cerium oxide, gadolinium chloride, gadolinium nitride, gadolinium carbonate, gadolinium oxide, zirconium chloride, zirconium nitride, zirconium oxide, zirconium carbonate, yttrium chloride, yttrium nitride, yttrium oxide, yttrium carbonate, or combinations thereof. For example, the precursor of the solid oxide electrolyte material may include cerium chloride (CeCl3), cerium nitrate (Ce(NO3)3), cerium carbonate (CeCO3), yttrium (III) tris(2,2,6,6-tetramethyl-3,5-heptanedione), yttrium chloride (YCl3), yttrium nitrate (Y(NO3)3), zirconium (IV) acetylacetonate (Zr(C5H7O2)4), zirconium tetrakis(2,2,6,6-tetramethyl-3,5-heptanedione), zirconium tetrachloride (ZrCl4), zirconium nitrate (Zr(NO3)4), gadolinium chloride (GdCl3), gadolinium nitrate (Gd(NO3)3), gadolinium carbonate (Gd2(CO3)3), or a combination thereof.

[0070] The metal that may be used in the vapor-liquid-solid growth method may include nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), gold (Au), copper (Cu), or a combination thereof.

[0071] A solid oxide cell according to some embodiments includes a solid oxide electrolyte and a fuel electrode on one side of the solid oxide electrolyte and an air electrode on an opposite side of the solid oxide electrolyte.

[0072] For example, the solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyte cell (SOEC), or both.

[0073] Figure 3 is a schematic diagram showing an embodiment in which the solid oxide cell is a solid oxide fuel cell 200 .

[0074] Reference Figure 3 The solid oxide fuel cell 200 includes: a fuel electrode 220; an air electrode 210 facing the fuel electrode 220; and an oxygen ion conductive solid oxide electrolyte 230 located between the fuel electrode 220 and the air electrode 210.

[0075] As shown in Reaction Formula 1, the electrochemical reaction of the solid oxide fuel cell 200 includes: oxygen O2 at the air electrode 210 is converted into oxygen ions O2 - An air electrode reaction and a fuel electrode reaction in which the fuel (H2 or hydrocarbon) of the fuel electrode 220 reacts with the oxygen ions that have passed through the electrolyte.

[0076] [Reaction formula 1]

[0077] Air electrode reaction: 1 / 2O2+2e - →O2 -

[0078] Fuel electrode reaction: H2+O2 - →H2O+2e -

[0079] In the air electrode 210 of the solid oxide fuel cell 200, oxygen adsorbed on the electrode surface is dispersed and moves toward the three-phase boundary where the solid oxide electrolyte 230, the air electrode 210 and the pores (not shown) intersect each other through surface diffusion to obtain electrons to become oxygen ions, and the generated oxygen ions move to the fuel electrode 220 through the solid oxide electrolyte 230.

[0080] In the fuel electrode 220 of the solid oxide fuel cell 200, the moving oxygen ions combine with the hydrogen contained in the fuel to generate water. At this time, hydrogen releases electrons to become hydrogen ions (H + ), hydrogen ion (H + ) combines with oxygen ions. The released electrons move to the air electrode 210 through a wire (not shown) and change oxygen into oxygen ions. Through this movement of electrons, the solid oxide fuel cell 200 can perform a battery function.

[0081] Figure 4 3 is a schematic diagram showing a case where the solid oxide battery is a solid oxide electrolyte battery 300 .

[0082] Reference Figure 4 The solid oxide electrolyte cell 300 includes: an air electrode 310; a fuel electrode 320 disposed facing the air electrode 310; and an oxygen ion conductive solid oxide electrolyte 330 disposed between the air electrode 310 and the fuel electrode 320.

[0083] As shown in Reaction Formula 2, the electrochemical reaction of the solid oxide electrolyte cell 300 includes converting water (H2O) of the fuel electrode 320 into hydrogen (H2) and oxygen ions (O2 - ) and an air electrode reaction in which oxygen ions passing through the solid oxide electrolyte 330 are converted into oxygen (O2). This reaction is opposite to the reaction principle of a conventional fuel cell.

[0084] [Reaction 2]

[0085] Fuel electrode reaction: H2O+2e - →O2 - +H2

[0086] Air electrode reaction: O2 - →1 / 2O2+2e -

[0087] When power is applied to the solid oxide electrolyte cell 300 from the external power source 340, the solid oxide electrolyte cell 300 is supplied with electrons from the external power source 340. The electrons react with the water supplied to the fuel electrode 320 to generate hydrogen and oxygen ions. The hydrogen is released to the outside, and the oxygen ions pass through the electrolyte 330 to reach the air electrode 310. The oxygen ions moved to the air electrode 310 lose electrons and then become oxygen and are released to the outside. The electrons flow to the external power source 340. Through this electron movement, the solid oxide electrolyte cell 300 can electrolyze water to form hydrogen at the fuel electrode 320 and oxygen at the air electrode 310.

[0088] The fuel electrodes 220 and 320 include a metal-solid oxide composite according to one aspect. This is the same as described above, and will not be described repeatedly.

[0089] Fuel electrodes 220 and 320 may also include solid oxide electrolyte material particles.

[0090] For example, the solid oxide electrolyte material particles may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0091] Fuel electrodes 220 and 320 may also include fuel electrode material particles.

[0092] For example, the fuel electrode material particles may include pure metals such as nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), or platinum (Pt), or oxides thereof.

[0093] In this case, the fuel electrodes 220 and 320 may include a metal ceramic in which the fuel electrode material particles and the solid oxide electrolyte material particles are combined. For example, when the solid oxide electrolyte material particles are yttria-stabilized zirconia (YSZ) and the fuel electrode material particles are nickel (Ni), the fuel electrodes 220 and 320 may include Ni / YSZ metal ceramics. When the fuel electrode material particles are ruthenium (Ru), the fuel electrodes 220 and 320 may include Ru / YSZ metal ceramics.

[0094] For example, the fuel electrodes 220 and 320 may have a thickness of 1 μm to 1000 μm or 5 μm to 100 μm.

[0095] The air electrodes 210 and 310 include an air electrode material. The air electrode material may be a material that reduces oxygen to oxygen ions.

[0096] For example, the air electrode material may include metal oxide particles having a perovskite crystal structure. Perovskite metal oxides are mixed ionic electronic conductor (MIEC) materials having both ionic conductivity and electronic conductivity, and have high oxygen diffusion coefficients and charge exchange reaction rate coefficients, allowing redox reactions to occur over the entire surface of the electrode, rather than just at the three-phase interface.

[0097] The perovskite type metal oxide may be represented by Chemical Formula 1.

[0098] [Chemical formula 1]

[0099] ABO 3±γ

[0100] In Chemical Formula 1, A is an element including La, Ba, Sr, Sm, Gd, Ca, or a combination thereof, B is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc, or a combination thereof, and γ represents oxygen excess or oxygen deficiency. For example, γ may be a number in the range of 0≤γ≤0.3.

[0101] For example, the perovskite type metal oxide may be represented by Chemical Formula 2.

[0102] [Chemical formula 2]

[0103] A' 1-x A” x B'O 3±γ

[0104] In Chemical Formula 2, A′ is an element including Ba, La, Sm, or a combination thereof, A″ is an element including Sr, Ca, Ba, or a combination thereof and is different from A′, B′ is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc, or a combination thereof, 0≤x<1, and γ represents oxygen excess or oxygen deficiency. For example, γ may be a number in the range of 0≤γ≤0.3.

[0105] For example, the air electrode material may include lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or combinations thereof.

[0106] The air electrodes 210 and 310 may also include a solid oxide electrolyte material.

[0107] For example, the solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0108] In this case, when the solid oxide electrolyte material is yttria-stabilized zirconia (YSZ) and the air electrode material is lanthanum strontium manganese oxide (LSM), the porous solid oxide composite may be a LSM-YSZ composite.

[0109] For example, the air electrodes 210 and 310 may have a thickness of 1 μm to 100 μm or 5 μm to 50 μm.

[0110] The solid oxide electrolytes 230 and 330 play a role in transporting the generated oxygen ions from the air electrodes 210 and 310 to the fuel electrodes 220 and 320 by ion conduction. The solid oxide electrolytes 230 and 330 have airtightness to prevent contact between air and the fuel electrodes 220 and 320, and also prevent the electrons generated at the fuel electrodes 220 and 320 from moving directly toward the air electrodes 210 and 310 due to high oxygen ion conductivity and low electron conductivity (high resistance, high insulation).

[0111] In addition, since the solid oxide electrolytes 230 and 330 have the air electrodes 210 and 310 and the fuel electrodes 220 and 320 on both sides thereof, and the air electrodes 210 and 310 and the fuel electrodes 220 and 320 have a very large oxygen partial pressure, it may be necessary to maintain the aforementioned properties in a wide oxygen partial pressure region.

[0112] The materials used for the solid oxide electrolytes 230 and 330 are not particularly limited as long as they are generally available in the art, and may include, for example, yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

[0113] For example, the solid oxide electrolytes 230 and 330 may have a thickness of 10 nm to 100 μm or 100 nm to 50 μm.

[0114] Optionally, the solid oxide cells 200 and 300 may further include a current collecting layer (not shown) including an electrical conductor located on at least one side of the air electrodes 210 and 310 (e.g., the outside of the air electrodes 210 and 310). The current collecting layer may serve as a current collector to collect electricity in the configuration of the air electrodes 210 and 310.

[0115] For example, the collector layer may include lanthanum cobalt oxide (LaCoO3), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), lanthanum strontium cobalt manganese oxide (LSCM), lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), or a combination thereof. The collector layer may use the materials listed above alone or in a combination of two or more, wherein these materials may be formed into a single layer or two or more layers having a stacked structure.

[0116] The solid oxide cells 200 and 300 may be manufactured by conventional methods known in various literatures in the art.

[0117] The solid oxide cells 200 and 300 may be applied to various structures, such as a cylindrical (tubular) stack, a flat tubular stack, a planar stack, and the like.

[0118] In addition, the solid oxide cells 200 and 300 may be in the form of a unit cell stack. For example, unit cells (membrane electrode assemblies (MEAs)) composed of air electrodes 210 and 310, fuel electrodes 220 and 320, and solid oxide electrolytes 230 and 330 are stacked in series, and separators electrically connected between the unit cells are provided to obtain a unit cell stack.

[0119] Hereinafter, specific examples of the embodiments are presented. However, the following examples are only intended to specifically illustrate or explain the embodiments, and the scope of the present disclosure should not be limited thereto.

[0120] [Foreseeable preparation example: Fabrication of solid oxide batteries]

[0121] 1) Preparation of metal-solid oxide composites

[0122] After placing the sample in the center of the chamber at a high temperature of 800°C under a low pressure of 0.04 atm, solid YCl3 powder and Zr(C5H7O2)4 powder were put into a high temperature boat and placed at the gas inlet side of the chamber. Subsequently, nitrogen and oxygen as carrier gases were supplied into the chamber at 100 sccm.

[0123] The precursor of the solid oxide electrolyte material is dissolved in Ni in the liquid phase at high temperature.

[0124] The precursor of the solid oxide electrolyte material was continuously supplied with a carrier gas at 100 sccm to reach a supersaturated state, and the supersaturated solid oxide electrolyte material was precipitated as a solid phase to grow nanowires.

[0125] When the nanowires grow to the desired length, the addition of the precursor of the solid oxide electrolyte material is stopped, and a metal-solid oxide composite is obtained.

[0126] 2) Fabrication of solid oxide unit cells

[0127] 100 g of the prepared metal-solid oxide composite powder and 1.5 g of a dispersant were added to 200 g of ethanol, and the mixture was ball-milled for 24 hours. Subsequently, a 10 wt % polyvinyl butyral ethanol solution and a phthalate plasticizer were added to the ball-milled material, and the mixture was ball-milled again for 24 hours to obtain a metal-solid oxide composite dispersion.

[0128] The fuel electrode support with the film attached at the bottom surface was immersed in the metal-solid oxide composite dispersion for 1 minute, lifted at a predetermined speed, and dried at room temperature for about 5 minutes. Herein, a metal-solid oxide composite fuel electrode layer having a thickness of 10 μm was formed on the upper surface of the fuel electrode support to which the film was not attached.

[0129] 100g of YSZ powder and 1.2g of dispersant were added to 300g of ethanol and then ball-milled for 24 hours. Subsequently, 10wt% polyvinyl butyral ethanol solution and phthalate plasticizer were added to the material obtained by ball milling, and then ball milled again for 24 hours to obtain a YSZ dispersion. The fuel electrode support having a fuel electrode layer thereon was immersed in the YSZ dispersion for 2 seconds, lifted at a predetermined speed, dried at room temperature for about 5 minutes, and fired at 1300°C for heat treatment to form a 5μm thick YSZ electrolyte layer on the fuel electrode layer.

[0130] 12g of YSZ powder and 12g of LSCF (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3) powder was added to 12g of ethanol, and the mixture was ball-milled for 24 hours. Subsequently, 10wt% ethyl cellulose / terpineol solution was added to the ball-milled material, and the mixture was roll-milled again to obtain GDC / LSCF paste. GDC / LSCF paste was screen-printed on the YSZ electrolyte layer of the fired half-cell and dried in an oven at 100°C for 0.5 hours to form a 15μm thick GDC / LSCF air electrode layer. Subsequently, firing was performed in a furnace at a high temperature of 1050°C in an air atmosphere for 2 hours to complete the unit cell.

[0131] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0132] <Description of Reference Numerals>

[0133] 10: Metal-solid oxide composite

[0134] 11: Nanowire part 12: Metal part

[0135] 13: Central part 14: Interface part

[0136] 200: Solid Oxide Fuel Cell

[0137] 210: Air electrode

[0138] 220: Fuel electrode

[0139] 230: Solid Oxide Electrolyte

[0140] 300: Solid Oxide Electrolyte Battery

[0141] 310: Air electrode

[0142] 320: Fuel electrode

[0143] 330: Solid Oxide Electrolyte

[0144] 340: External power supply

[0145] Industrial Applicability

[0146] The present disclosure relates to a metal-solid oxide composite, a method for preparing the same, and a solid oxide cell including the metal-solid oxide composite, wherein the solid oxide cell improves cell performance and efficiency by using a fuel electrode material having a structure in which coarsening is prevented during high temperature operation and specific surface area is increased without interfering with gas flow.

Claims

1. A metal-solid oxide composite comprising: a plurality of nanowire portions including a solid oxide electrolyte material; a metal portion disposed on at least one of the plurality of nanowire portions and including a metal; and A central portion is connected to opposite ends of each of the plurality of nanowire portions. 2 . The metal-solid oxide composite according to claim 1 , having a shape in which the plurality of nanowire portions radially extend from the central portion.

3. The metal-solid oxide composite according to claim 1, wherein The metal-solid oxide composite has an average size of 0.5 μm to 10 μm, and The dimension of the metal-solid oxide composite is the longest straight line from one of the metal portions to another of the metal portions.

4. The metal-solid oxide composite according to claim 1, wherein The plurality of nanowire parts have a nanowire shape, and have an average length of 0.2 μm to 3 μm and an average diameter of 10 nm to 500 nm.

5. The metal-solid oxide composite according to claim 1, wherein The metal portion has an average size of 10 nm to 500 nm, and The average size of the metal portion is a length perpendicular to a length direction of one nanowire portion among the plurality of nanowire portions attached to the metal portion.

6. The metal-solid oxide composite according to claim 1, wherein The solid oxide electrolyte material includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3) or a combination thereof.

7. The metal-solid oxide composite according to claim 1, wherein The metal portion includes nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), gold (Au), copper (Cu), oxides thereof, or a combination thereof.

8. The metal-solid oxide composite according to claim 1, wherein The metal-solid oxide composite includes 20 to 80 parts by weight of the metal based on 100 parts by weight of the solid oxide electrolyte material.

9. The metal-solid oxide composite according to claim 1, wherein The metal-solid oxide composite further comprises: An interface portion is disposed between the nanowire portion and the metal portion and includes a mixture of the solid oxide electrolyte material and the metal.

10. A method for preparing the metal-solid oxide composite according to claim 1, comprising: The plurality of nanowire portions are grown by using vapor-liquid-solid (VLS) growth in which the metal is a catalyst and a vapor-phase precursor of the solid oxide electrolyte material is supplied.

11. The method according to claim 10, wherein: The vapor-liquid-solid (VLS) growth comprises: supplying a precursor of the solid oxide electrolyte material in a gas phase to a space under a high temperature and low pressure state; dissolving the precursor of the solid oxide electrolyte material in a metal in a liquid phase; continuously supplying the precursor of the solid oxide electrolyte material to reach a supersaturated state; and The supersaturated solid oxide electrolyte material is precipitated as a solid phase to grow the plurality of nanowire portions.

12. The method according to claim 11, wherein: The high temperature and low pressure state is a temperature of 500° C. to 1200° C. and a pressure of 0.03 atm to 1 atm.

13. The method according to claim 10, wherein: The precursor of the solid oxide electrolyte material includes cerium chloride, cerium carbonate, cerium oxide, cerium nitride, gadolinium nitride, gadolinium chloride, gadolinium carbonate, gadolinium oxide, zirconium chloride, zirconium nitride, zirconium oxide, zirconium carbonate, yttrium chloride, yttrium nitride, yttrium oxide, yttrium carbonate or a combination thereof.

14. The method according to claim 10, wherein: The metal includes nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), gold (Au), copper (Cu), or a combination thereof.

15. A solid oxide battery comprising: solid oxide electrolyte; and a fuel electrode and an air electrode, the fuel electrode being on one side of the solid oxide electrolyte and the air electrode being on an opposite side of the solid oxide electrolyte, Wherein, the fuel electrode includes a metal-solid oxide composite, and the metal-solid oxide composite includes: a plurality of nanowire portions, including a solid oxide electrolyte material; a metal portion, located at one end of each of the plurality of nanowire portions and including a metal; and a central portion, connected to the other end of the nanowire portion.

16. The solid oxide battery according to claim 15, wherein: The fuel electrode further includes fuel electrode material particles, and the fuel electrode material particles include nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), oxides thereof, or combinations thereof.

17. The solid oxide battery according to claim 15, wherein: The fuel electrode also includes solid oxide electrolyte particles, which include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

18. The solid oxide battery according to claim 15, wherein: The air electrode comprises an air electrode material, wherein the air electrode material comprises lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide or a combination thereof.

19. The solid oxide battery according to claim 15, wherein: The solid oxide electrolyte includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), bismuth oxide (Bi2O3), or a combination thereof.

20. The solid oxide battery according to claim 15, wherein: The solid oxide cell is a solid oxide fuel cell (SOFC), a solid oxide electrolyte cell (SOEC), or both.

Citation Information

Patent Citations

  • Electric mosquitoes, pest control windows and coverings

    KR1020220169583A

  • Method and system for adapting programs for interoperability and adapters therefor

    KR1020230021185A